IEEE PES Innovative Smart Grid Technologies, Europe 2014
DOI: 10.1109/isgteurope.2014.7028910
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in real-time voltage stability assessment methods based on Thévenin equivalent due to PMU's accuracy

Abstract: This article studies the influence of PMU's accuracy in voltage stability assessment, considering the specific case of Thévenin equivalent based methods that include wide-area information in its calculations. The objective was achieved by producing a set of synthesized PMU measurements from a time domain simulation and using the Monte Carlo method to reflect the accuracy for the PMUs. This is given by the maximum value for the Total Vector Error defined in the IEEE standard C37.118. Those measurements allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Thereby this paper focus on computational performance only. For studies on the impact of measurement uncertainty the reader is referred to [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby this paper focus on computational performance only. For studies on the impact of measurement uncertainty the reader is referred to [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that a higher percentage of power generation will come from wind energy in Denmark [1] and its variability will impose challenges in the power system control and stability, where some of those concerns are aimed to be addressed by the SOSPO project 1 . For this purpose, a set of algorithms have been developed to produce a fast stability assessment, in real-time, by using PMU (Phasor Measurement Units) and wide-are information [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of voltage stability, two methods were identified as suitable for real-time assessment [5]: sensitivities and Thévenin Equivalent methods, and a review of existent approaches can be found in [11]. The real-time voltage stability assessment in this paper is based on Thévenin equivalent method [2,5,11], which offers advantages in its computational complexity [5] and its element-wise nature is used to consider the limits in the generators as described in [6]; the improvements described in [9] make it suitable for considering wind farms limits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every measurement has some noise component. While PMUs are capable of measuring state variables directly it has been shown that the noise component can reduce the accuracy of system monitoring to undesirable levels [2]. A state estimator may filter the noise component from the measurements.…”
Section: Introductionmentioning
confidence: 99%